Penampilan Vegetatif dan Produksi Hijauan Berbagai Aksesi Arbila (Phaseolus lunatus L.) dari Kabupaten Kupang Sebagai Pakan: Vegetative Performance and Forage Production of Various Accesses of Arbila (Phaseolus lunatus L.) from Kupang District as Feed - Bernadete Barek Koten; Sondang Leoanak; Redempta Wea; Allan P. Titong (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2022)
Abstract  The study aimed to evaluate the vegetative appearance and performance of arbila (Phaseolus lunatus L.) from Kupang Regency which was used as feed. Research was carried out in Politani land for 6 months, with 43 accessions and 3 replications. The variables observed were root length, root weight, number of root nodules, percentage of effective root nodules, root nodule diameter, number of green leaves per plant, individual leaf area, leaf weight, stem length, stem diameter, stem weight, number of shoots, and weight of top plant. The results showed that overall, root length was 19–52 cm, root weight was 15–110 g/plant, number of nodules ranged from 0–257 pieces, percentage of effective nodules ranged from 0–100%, and nodule diameter was 0.11–0.98 cm. The number of green leaves ranged from 29.5–128.5 fruit/plant, leaf area 8.11–38.17 cm2, leaf weight ranged from 16–199.5 g/tree. Stem length ranged from 144-358 cm/plant, stem diameter ranged from 0.15 to 0.75 cm, stem weight ranged from 26 to 130.5 g/plant, shoots ranged from 3.5 to 28 shoots/plant, and plant weight of the top plant are 29-316 g/plant. It was concluded that there were differences in the vegetative parts of arbila as seen from the performance of roots, stems, and leaves of various accessions. Accession K10 showed the best root performance, and accession K8, K19 and K45 showed the best shoots, stem, and leaf performance, and forage production as feed.   Keywords: Arbila legume; Feed; Number of shoots; Root nodule; Vegetative   Abstrak  Penelitian yang bertujuan untuk mengevaluasi penampilan bagian vegetatif dan performa arbila (Phaseolus lunatus L.) yang berasal dari Kabupaten Kupang yang terbaik sebagai pakan, telah dilaksanakan di lahan Politani selama 6 bulan, dengan 43 jumlah aksesi dan 3 ulangan. Variabel yang diamati adalah panjang akar, bobot akar, jumlah bintil akar, persentasi bintil akar efektif, diameter bintil akar, jumlah daun hijau per tanaman, luas individu daun, bobot daun, panjang batang, diameter batang, bobot batang, jumlah tunas, dan bobot tanaman bagian atas. Data dianalisis dan dideskripsikan. Hasil penelitian menunjukkan bahwa secara keseluruhan, panjang akar 19–52 cm, bobot akar 15–110 g/tanaman, jumlah bintil berkisar 0–257 buah, persentasi bintil efektif berkisar antara 0–100 %, dan diameter bintil 0,11–0,98 cm. Jumlah daun hijau berkisar 29,5–128,5 buah/tanaman, luas daun 8,11–38,17 cm2, bobot daun berkisar 16–199,5 g/pohon. Panjang batang berkisar 144-358 cm/tanaman, diameter batang berkisar 0,15–0,75 cm, bobot batang berkisar antara 26–130,5 g/tanaman, jumlah tunas berkisar 3,5–28 tunas/tanaman, dan bobot tanaman bagian atas adalah 29-316 g/tanaman. Disimpulkan bahwa terdapat perbedaan bagian vegetatif arbila yang terlihat dari performa akar, batang, dan daun dari berbagai aksesi arbila. Aksesi K10 memperlihatkan performa akar terbaik dan aksesi K8, K19 dan K45 memperlihatkan performa tunas, batang dan daun dan produksi hijauan terbaik sebagai pakan ternak.   Kata Kunci: Bintil akar; Jumlah tunas, Legum Arbila; Pakan; Vegetatif.